2013
DOI: 10.3141/2388-05
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Injury Outcomes of Crashes Involving Heavy Vehicles on Texas Highways

Abstract: Concern related to crashes that involve large trucks has increased in Texas recently because of the potential economic impacts and level of injury severity that can be sustained. However, detailed studies on large truck crashes that highlight the contributing factors leading to injury severity have not been conducted in Texas, especially for its Interstate system. The contributing factors related to injury severity were analyzed with Texas crash data based on a discrete outcome-based model that accounts for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 59 publications
7
28
1
Order By: Relevance
“…These drowsy events would increase a driver's susceptibility to a crash and therefore, would likely increase both the frequency of heavy truck crashes and the severity of heavy truck crashes during these times of the day. Heavy truck crashes occurring between 3 p.m. and 7 p.m. were less likely to result in an injury (Islam and Hernandez, 2013). The same study revealed that the likelihood of non-incapacitating injuries was lower for crashes occurring during the fall season (September-December).…”
Section: Crash Specific Characteristicssupporting
confidence: 58%
See 4 more Smart Citations
“…These drowsy events would increase a driver's susceptibility to a crash and therefore, would likely increase both the frequency of heavy truck crashes and the severity of heavy truck crashes during these times of the day. Heavy truck crashes occurring between 3 p.m. and 7 p.m. were less likely to result in an injury (Islam and Hernandez, 2013). The same study revealed that the likelihood of non-incapacitating injuries was lower for crashes occurring during the fall season (September-December).…”
Section: Crash Specific Characteristicssupporting
confidence: 58%
“…Past studies (Islam and Hernandez, 2013;Lemp et al, 2011, Qin et al, 2013Bham et al, 2012) found a negative correlation between adverse road conditions, such as rain or snow, and crash severity, suggesting that the decline in severity under adverse roadway and weather conditions is attributable to drivers being more cautious under such conditions. However, Islam et al (2014) found that inclement weather, such as fog or mist, increased the probability of a major injury in urban single vehicle heavy truck crashes.…”
Section: Roadway and Environmental Factorsmentioning
confidence: 94%
See 3 more Smart Citations